Grating Coupler for an On-Chip Lithium Niobate Ridge Waveguide - Muhammad Shemyal Nisar; Xiangjie Zhao; An Pan; Shui Yuan; JinSong Xia (IEEE Photonics Journal)
We report simulation and fabrication of a grating coupler for coupling of light between an on-chip lithium niobate ridge waveguide and an optical fiber. A grating coupler with an insertion loss of less than 10 dB for C-band frequencies (1530–1565 nm) was achieved.